Language Variation in College Students: Sociolinguistics Perspective - Anisa Anggraini Putri (CV. Tirta Pustaka Press, 2024)
This research was proposed to reveal and analyze the language variations used and how college students utilize these variations daily conversation. This research employed a qualitative descriptive method. The main data of this research was the written status uploaded by college students on social media: Facebook and Instagram. The researcher then cited and captured students' posts representing language variation, classifying the types of language variations including slang, code switching & mixing, gender, colloquial language, formal & informal context, dialect to describe how the language was used. Documentation represents the final technique of data collection. The data was analyzed using Miles and Huberman theories (2014). It included collecting, reducing, classifying, and drawing conclusions from data. The validity of the data used in this study was triangulation of sources, methods, and theory. Based on the conclusion is included in the type of regional dialect, because it is a variant of the language used in a particular area. For example, Indonesian Makassar dialect, Jakarta dialect of Bali dialect etc. Although the dialects used in each region can be united with Indonesian to communicate both formally and informally. It's just that there is a difference in emphasis on the letters of a particular letter in each dialect. The intonation of sounds used in pronunciation also tends to vary from region to region. However, this does not affect in Indonesian language.